2022
DOI: 10.1186/s12917-022-03343-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of new and old biomarkers in dogs with degenerative mitral valve disease

Abstract: Background Dogs with degenerative mitral valve disease are commonly presented to small animal clinicians. Diagnosis, clinical staging, and therapeutic design are based on a combination of clinical examination, radiography, and echocardiography. To support diagnosis and clinical monitoring, a multi-marker-based approach would be conceivable. The aim of this study was to investigate the suitability of Galectin-3 and interleukin-1 receptor-like 1 protein (ST2) in dogs with degenerative mitral valv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
(67 reference statements)
0
5
0
1
Order By: Relevance
“…Although ST2 proved to be an unspecific marker, recent studies on myxomatous degeneration suggest that the cytokine interleukin-33/ST2 pathway may be amplifying extracellular matrix remodeling in mitral valves [ 27 ]. Unfortunately, studies investigating circulating ST2 concentrations in canine MMVD [ 17 , 28 ], including our study, have, up to now, not been successful in showing significant differences between healthy and diseased states. Further research is needed before definitive conclusions.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although ST2 proved to be an unspecific marker, recent studies on myxomatous degeneration suggest that the cytokine interleukin-33/ST2 pathway may be amplifying extracellular matrix remodeling in mitral valves [ 27 ]. Unfortunately, studies investigating circulating ST2 concentrations in canine MMVD [ 17 , 28 ], including our study, have, up to now, not been successful in showing significant differences between healthy and diseased states. Further research is needed before definitive conclusions.…”
Section: Discussionmentioning
confidence: 75%
“…The cTnI and NT-ProBNP were implemented for detection of myocardial injury and ventricular wall stress in dogs. A study by Kuleš et al showed higher serum concentrations of these two markers in dogs diagnosed with MMVD stage C compared to healthy dogs [ 9 ] and other MMVD stages [ 17 ]. Since echocardiography and radiography (the gold diagnostic standards for canine MMVD) and veterinary cardiologists are primarily situated in larger clinics, this, as well as increased costs of examination, limit the access for some dog owners.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of diagnostic test for heart disease in dogs is an important stage in the examination of the animal [4][5][6][7]. One of the most accessible and informative methods is echocardiography, which allows one to evaluate the structures of the heart, such as the valve apparatus, heart chambers and great vessels [7][8][9][10][11]. In this regard, the purpose of the study is to evaluate the role of visual diagnostics in establishing the stages of development of mitral valve insufficiency in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarker measurement is of interest as a possible alternative method for early detection of various diseases ( 12 ). N-terminal pro B-type natriuretic peptide (NT-proBNP) and cardiac troponin I (cTnI) have become significant in the veterinary cardiovascular field ( 13 ). However, these proteins are mainly used as additional diagnostic tools for MMVD ( 14 ) and are insufficient as biomarkers to detect PH in dogs ( 15–17 ).…”
Section: Introductionmentioning
confidence: 99%